Performance of referral recommendations in patients with chronic back pain and suspected axial spondyloarthritis. Issue 11 (24th April 2007) - Brandt, Henning Christian; Spiller, Inge; Song, In-Ho; Vahldiek, Janis L; Rudwaleit, Martin; Sieper, Joachim
Abstract : Background: Ankylosing spondylitis (AS) and its early form account for up to 5% of all patients with chronic back pain. Interest has recently focused on shortening the delay of 5–10 years between the appearance of first symptoms and the diagnosis of AS, particularly because effective treatments have now become available. Referral parameters that are easy for doctors in primary care to apply to patients presenting with possible AS could contribute to earlier diagnosis. Methods: Orthopaedists and primary-care doctors were requested to refer patients with (1) chronic low back pain (duration >3 months) and (2) onset of back pain before <45 years of age to a specialist rheumatology outpatient clinic for further diagnostic investigation if at least one of the following screening parameters was present: (1) inflammatory back pain, (2) positive human leucocyte antigen B27, and (3) sacroiliitis detected by imaging. The final diagnosis was made according to expert opinion. Results: In total, 350 referred cases were analysed. A diagnosis of definite axial spondyloarthritis (axial SpA), comprising established AS and pre-radiographic axial SpA, could be made in 45.4% of all referred patients (of which 50.3% were classified as AS and 49.7% as preradiographic axial SpA), whereas 45.4% were classified as non-SpA and 9.1% as possible SpA. A diagnosis of definite axial SpA could be made in 34.2% if only one referral parameter was positive, and in 62.6% if there was >1 positive referral parameter. Conclusions: The proposed referral parameters have proven useful when applied in primary care in identifying patients with AS/pre-radiographic axial SpA among young to middle-aged patients with chronic low back pain.